The implementation of ESL in-service training in Kota Belud primary schools: A study of the selected english teachers - Krishna K.S. @ Mohd. Fadzli Abdul Rozan (2006)
The purpose of this research were to identify whether Kota Belud Year 6 English teachers who attended the Contemporary Literature Course organized by Kota Belud District Education Office conducted in-service training in their respective schools and to identify factors that help or inhibit these teachers from conducting in-service training in their respective schools. 57 Year Six English teachers from 57 primary schools in Kata Belud were selected as sample of this research. Statistical Package for Social Science (SPSS) version 13. 0 was used to analysis data collected. Correlation test was used to identify relationship between independent variables- Individual/Personal Factors and Organizational Factors- and dependent variable- the conducting of in-service training. The findings of the research showed that there was no significant difference between male and female teachers in the implementation of in-service training based on Pearson Chi-Square (x2 '=2. 74, k>0.05). In addition, the research showed that there was a strong positive significant relationship (r=0. 810, k<0. 01 ), based on Pearson Correlation test, between individual/personal factors and the conducting of in-service training among the teachers involved. However, the research discovered that there was no significant relationship (r=-0.198, k>0. 01) between the organization factors and the conducting of inservice training. Besides that, the research found that there was a low negative significant relationship (r=-0. 272, k<0. 01) between individual/personal factors and organizational factors.